2010
DOI: 10.1007/bf03091811
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous mitral valve repair using the edge-to-edge technique in a high-risk population

Abstract: 437orIgInAl ArtIcle percutaneous mitral valve repair using the edge-to-edge technique in a high-risk population Background. Percutaneous mitral valve (MV) repair using the edge-to-edge clip technique might be an alternative for patients with significant mitral regurgitation (MR) and an unacceptably high risk for operative repair or replacement. We report the short-term safety and efficacy of this new technique in a high-risk population. Methods. All consecutive high-risk patients who underwent percutaneous MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…As in previous studies, clip embolization was not observed in the present registry. In fact, only a single case of clip embolization has been reported worldwide, so far [1,[3][4][5]8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table V). Partial clip detachment from one leaflet was rarely observed (2% in the present analysis) and occurred spontaneously or during advancement of a second clip for residual MR.…”
Section: Discussionmentioning
confidence: 99%
“…As in previous studies, clip embolization was not observed in the present registry. In fact, only a single case of clip embolization has been reported worldwide, so far [1,[3][4][5]8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table V). Partial clip detachment from one leaflet was rarely observed (2% in the present analysis) and occurred spontaneously or during advancement of a second clip for residual MR.…”
Section: Discussionmentioning
confidence: 99%
“…Procedural technique. All procedures were performed as previously described (14). In brief, the clip device system is delivered to the left atrium (LA) via a transseptal puncture, advanced into the LV, and then retracted during systole, grasping the MV leaflets.…”
Section: Methodsmentioning
confidence: 99%
“…Early data from EVEREST (Endovascular Valve Edge-to-Edge REpair Study) studies suggest that valve repair with the MitraClip System is feasible, safe and associated with procedural and mid-term outcomes not inferior to surgical treatment [6][7][8][9]. Recent data from experienced centers have attested to the safety and efficacy of this procedure in a high surgical risk, "real-world" population [10][11][12].…”
Section: Introductionmentioning
confidence: 99%